Developing a Cloze Procedure as a Reading Comprehension Achievement Test - I Ketut Seken (TEFLIN Journal: A publication on the teaching and learning of English, 2004)
The project was concerned with developing a cloze procedure as a reading comprehension achievement test. The subjects were students of the English Department of the Faculty of Letters, State University of Malang, who were halfway in the semester to complete Reading II course. The test was planned and constructed on the foundation of existing theory of cloze test construction. A review of theory concerning reading comprehension, testing reading comprehension, and cloze testing led to the construction of the test, including the decision concerning how to score the test and to interpret the scores. Using a class of 28 students, the test was tried out a week after the mid-semester test was administered by the Reading II teacher. It was found that the test is sufficienty reliable on the basis of a reliability coefficient of .79 through split-half procedure and a coefficient value of .78 by K-R 20. The test also showed high inter-section correlation. The validity of the test was viewed in terms of face, content, and construct. The test scores correlate moderately with those obtained from the mid-semester test by the teacher. Some problems are discussed and a suggestion made with regard to a possible solution to these problems.